Rapid Entire Body Postural Analysis Assessment Device for Computer Operators - Fathima, Ahmadi; Shree, Mamatha; L, Pavithra G; Z, Tanzeeya V; S, Kavya (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2017)
The aim of this review is to provide a summary of one of the observational postural analysis ergonomic assessment tools; Rapid Entire Body Assessment (REBA) in terms of its development, applications, validity and limitations. Research showed REBA’s convenience for postural assessment of jobs in numerous professional settings, including industrial and health care jobs, construction, sawmill tasks, supermarket industry, food industry, computer based jobs, packaging, school workshop, odonatological services and for firefighters and emergency medical technicians. Face validity is established in two stages. In terms of concurrent validity, several studies used REBA to compare the results with other observational and direct methods so that the level of conformity between the two is determined. The limitations discussed in this review did not hold the method’s implementation back, on the contrary, it is currently used and remains a rapid to use tool with computerized checklist and tables available in public domain.